A Proposal for Making Monetary Management Effective in the United States - Hart, Albert G. (Review of Economic Studies, 1935)
Journal Article The "Chicago Plan" of Banking Reform: I A Proposal for Making Monetary Management Effective in the United States Get access Albert G. Hart Albert G. Hart Chicago Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 2, February 1935, Pages 104–116, https://doi.org/10.2307/2967557 Published: 01 February 1935